KEBIJAKAN FISKAL DALAM PERSPEKTIF ISLAM - Maryam Batubara; Dea Sarah Sati Hana’an (ITB AAS Indonesia Surakarta, 2023)
Fiscal policy is a policy that has strategies and rules carried out by the government to maintain state revenues and expenditures to remain stable so that the state can encourage economic development. Fiscal policy can affect a country's economy through changes in government revenues and expenditures that have been set in the state budget. In Islamic economics, fiscal policy is one of the tools to achieve the welfare of humanity as a whole. Basically, fiscal policy in Islamic and modern economics has differences in achieving prosperity. This research method uses literature studies. The results of this discussion show that fiscal policy in the Islma economy is expected to carry out the functions of allocation, distribution and stabilization within a country, in addition to budget income can be managed through Baitul Mal.